Analytical Solutions to the Coupled Boussinesq-Burgers Equations via Sine-Gordon Expansion Method - Ali, Karmina K.; Yilmazer, Resat; Bulut, Hasan (Springer International Publishing Ag, 2020)
In the current study, we investigate the coupled Boussinesq-Burgers equations through sine-Gordon expansion method. BBEs arises in the research of fluid flow and describes the spreading of shallow water waves. A traveling wave transformation has been applied to turn the governing equation into a nonlinear ordinary differential equation. As a result, we produce some novel analytical solutions, such as topological, non-topological, and kink-type soliton solutions. Furthermore, 2D, 3D and contour surfaces are also plotted for all obtaining solutions.
4th International Conference on Computational Mathematics and Engineering Sciences (CMES) -- APR 20-22, 2019 -- Akdeniz Univ, Antalya, TURKEY
Keywords: Analytical solutions; Coupled Boussinesq-Burgers equations; Sine-Gordon expansion method